ANALISIS KEMAMPUAN GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN VARIATIF DI KELAS TINGGI SD NEGERI 1 BALANGNIPA KECAMATAN SINJAI UTARA KABUPATEN SINJAI - Sitti Jauhar; Sudarto Sudarto; Andi Dhodi Yusuf (Jurnal Inovasi Penelitian, 2023)
This research is a type of qualitative descriptive research that aims to find out how the teacher's ability to use various learning media in the high grades of SD Negeri 1 Balangnipa, North Sinjai District, Sinjai Regency. The subjects in this study were teachers of grades IV, V and VI of SD Negeri 1 Balangnipa. Data collection was carried out by means of interviews and observation, data were analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the high-grade teachers based on pedagogical competence in terms of educational implementation are able to use varied learning media marked by the teacher's ability to use technology-based learning media, use learning media with sufficient time, use two or more types of media in turns, carry out learning activities in accordance with the plans that have been prepared, carry out learning activities with sufficient time for learning activities, and identify and use varied learning media consisting of audio, visual, audiovisual, and multimedia media in turns. The conclusion from the results of this study is that the high grade teachers based on pedagogical competence in terms of implementing learning that educates are able to use a variety of learning media